WHAT IS SOCIAL MEDIA ADDICTION EFFECT TO RISKY SEXUAL BEHAVIOR AMONG ADOLESCENTS ? - Ukhudiah Kafanila Malika Azar; Azimatul Karimah; Bagus Setyoboedi (UNIVERSITAS AIRLANGGA, 2026)
Background: In the era of Society 5.0, rapid advancements in digital technology have increased the use of social media, making it an integral part of daily life, particularly among adolescents. Adolescents are considered a vulnerable group due to their high exposure to social media content, including pornographic material, which may influence risky sexual behaviors. Therefore, this study aimed to examine the association between social media addiction and risky sexual behavior among adolescents at a senior high school in Sidoarjo, east java Indonesia. Method: This study used an analytic observational design with a cross-sectional approach. A total of 86 students were selected through purposive sampling. Data were collected using structured questionnaires assessing social media addiction and risky sexual behavior. Data analysis was conducted using the Chi-square test to determine the association between variables. Result: Most adolescents had a moderate level of social media addiction. A total of 48 students (55.8%) were categorized as engaging in risky sexual behaviors. The results showed that there was no significant association between social media addiction and risky sexual behavior (p = 0.905). However, the duration of social media use specifically Facebook, Twitter, and Instagram was significantly associated with both risky sexual behavior and the level of social media addiction (p < 0.05). Conclusion : Social media addiction was not significantly associated with risky sexual behavior among adolescents. However, the duration of social media use was found to be an important factor. Therefore, enhancing digital literacy and strengthening reproductive health education are recommended to reduce the potential negative impacts of social media on adolescents.